Structural and segregation analysis of the type II collagen gene (COL2A1) in some heritable chondrodysplasias. Issue 8 (August 1988) - Wordsworth, P; Ogilvie, D; Priestley, L; Smith, R; Wynne-Davies, R; Sykes, B
Abstract : Seventy-seven persons with a variety of heritable chondrodysplasias were screened for gross rearrangements of the structural gene encoding the major cartilage collagen, collagen II. None was found. Segregation of the locus (COL2A1) was studied in 19 pedigrees using three restriction site dimorphisms (shown by PvuII, HindIII, and BamHI) and a length polymorphism as linkage markers. Discordant segregation between COL2A1 and the mutant locus was seen in pedigrees with multiple epiphyseal dysplasia, autosomal recessive spondyloepiphyseal dysplasia tarda, hypochondroplasia, pseudoachondroplasia, diaphyseal aclasis, and trichorhinophalangeal syndrome. One pedigree with diastrophic dysplasia was weakly concordant. Autosomal dominant spondyloepiphyseal dysplasia tarda and metaphyseal chondrodysplasia (type Schmid) were not informative. We conclude that mutations of the collagen II gene are not a common feature of the heritable chondrodysplasias. Since the chondrocyte binding protein, chondrocalcin, is also encoded at COL2A1 our conclusions apply equally to this gene.